(untitled) (Revista Contexto & Saúde, 2022)
This study aims to investigate whether there is an association between body image, self-esteem, perception of aging, postural balance and handgrip strength in elderly women after practicing Pilates in Water. Descriptive, quasi-experimental study, with a sample composed of sedentary elderly women with preserved cognitive and functional independence. The instruments Body Appreciation Scale (BAS), Rosenberg’s Self-Esteem Scale, Aging Perceptions Questionnaire (APQ), TUG (Timed up and go) and the manual dynamometer were used. The PA protocol was divided into warm-up, strengthening in general and stretching. Statistical analysis was performed using Pearson’s correlation coefficient and Spearman’s correlation test, and the intensity was classified by Malina’s criterion. 33 elderly women (71.5 ± 5.48 years old), overweight (27.02 ± 4.42) and good body image, self-esteem and perception of aging participated in this study. They also had a low risk of falls and low handgrip strength. The elderly women presented, after the Pilates in Water exercises protocol, a moderate association between body image and perception about aging with regard to positive beliefs about how to deal with aging. Still, a high association was observed between postural balance and handgrip strength. It is concluded that these data are important because means must be directed to provide healthy aging and quality of life for the elderly.